Are you lookin' at me? A mixed-methods case study to investigate the influence of coaches' presence on performance testing outcomes in male academy rugby league players. Issue 2 (April 2023) - Richardson, Ben; Dobbin, Nick; White, Christopher; Bloyce, Daniel; Twist, Craig
The study used a mixed-methods approach to examine how the presence of coaches influenced male academy rugby league players' performance during physical performance testing. Fifteen male rugby players completed two trials of 20 m sprint, countermovement jump and prone Yo-Yo test; one with only the sport scientist present and a second where the sport scientist conducted the battery with both the club's lead strength and conditioning coach, academy manager, and the first team assistant and head coach present. Players and coaches then completed one-to-one semi-structured interviews to explore their beliefs, attitudes and opinions towards physical performance testing. In all tests, the players' performance was better when the coaches were present compared to when tests were conducted by the sport scientist alone. Interviews revealed performance testing was used by coaches to exercise their power over players to socialise them into the desired culture. Players' own power was evident through additional effort during testing when coaches were present. Practitioners should ensure consistency in the presence of significant observers during performance testing of male rugby players to minimise their influence on test outcome.